Illustration of trial procedure for the second experiment. - Cameron Smith (244750) (2025)
The cue shown is an arrow, but in Experiment 1 the cue was a face with eyes pointing to either the left or the right. The face is not shown here for copyright reasons. Target gratings had a contrast of 50%, plus a 10% increment in either the upper or lower half. Note that images are not drawn to scale in this schematic to aid visibility - see text for actual dimensions.